2019
DOI: 10.1002/mnfr.201900797
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Probiotics in the Prevention and Treatment of Atherosclerosis

Abstract: Atherosclerosis, the underlying cause of cardiovascular diseases such as myocardial infarction, cerebrovascular accident, and peripheral vascular disease, is the leading cause of global mortality. Current therapies against atherosclerosis, which mostly target the dyslipidemia associated with the disease, have considerable residual risk for cardiovascular disease together with various side effects. In addition, the outcomes from clinical trials on many promising pharmaceutical agents against atherosclerosis (e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 110 publications
(333 reference statements)
1
50
0
3
Order By: Relevance
“…[1][2][3] Current therapies against atherosclerosis such as statins are not fully effective and many promising pharmaceutical leads from various drug discovery and other screening programs have failed because of safety concerns and/or off-target effects. [1,2] Substantial interest has therefore been fuelled in the use of natural products in the prevention and treatment of atherosclerosis, possibly as adds-on with pharmaceutical agents. [1,2] Probiotic bacteria have many health benefits, including regulation of atherosclerosis-associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Current therapies against atherosclerosis such as statins are not fully effective and many promising pharmaceutical leads from various drug discovery and other screening programs have failed because of safety concerns and/or off-target effects. [1,2] Substantial interest has therefore been fuelled in the use of natural products in the prevention and treatment of atherosclerosis, possibly as adds-on with pharmaceutical agents. [1,2] Probiotic bacteria have many health benefits, including regulation of atherosclerosis-associated risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Current therapies targeting the dyslipidemia associated with atherosclerosis have various side effects. In comparison to pharmaceutical agents, nutraceuticals generated from the food after fermentation by probiotic bacteria have evoked greater interest in atherosclerosis prevention [ 90 ]. Supplementation of probiotic L. mucosae A1 exhibited effectiveness in the treatment of hyperlipidemia and atherosclerosis and improved gut microbiota dysbiosis, including increased richness and diversity in ApoE -/- mice on a Western diet [ 91 ].…”
Section: Probiotics and Their Potential Role In Cvdmentioning
confidence: 99%
“…It is likely that inflammatory processes play an important role in the pathogenesis and progression of atherosclerosis, as elevated levels of proinflammatory cytokines have been observed in patients with atherosclerosis [ 42 ]. However, although some studies have demonstrated that probiotics can decrease the production of pro-inflammatory cytokines, their underlying mechanism remains unclear [ 7 ].…”
Section: Probioticsmentioning
confidence: 99%
“…For example, it is known that a diet high in fruits and vegetables can decrease the risk of CVD via various mechanisms, including reducing plasma cholesterol level and inhibiting blood platelet activation. However, such dietary modification can also result in changes in the microbial and metabolic composition of the intestines, which themselves are known to be characteristic of a range of physiological and pathological states, including CVD; the composition of the gut microbiota has been found to be associated with atherogenesis, thrombosis, chronic heart conditions and arterial hypertension [ 3 , 4 , 5 , 6 , 7 ], and this correlation has also been noted in a recent meta-analysis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%